ANÁLISE DO DESEMPENHO TÉRMICO DE HABITAÇÕES DE INTERESSE SOCIAL EM COLATINA-ES COM BASE NA CARTA BIOCLIMÁTICA DE GIVONI - Malta, Nayara Salera; Amorim, Alexandre Cypreste (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Quality housing is the right of all citizens. However, several current examples of housing, especially those aimed at the low-income population, present flaws in terms of thermal comfort. The inefficiency detected often originates in the absence of individualized planning of housing. The objective of this research was to analyze the thermal performance of housing of social interest, in the city of Colatina-ES, having as main parameter of analysis the bioclimatic chart of Givoni. The dwellings of the Renzo Morelato Housing Set were also evaluated in the design phase, in comparison to the recommendations prescribed in NBR 15220-3/2005. Measurements of temperature, humidity and wind velocity were also carried out. The results showed that the social housing in Colatina does not count on thermal performance considered adequate to ZB8, where they are implanted. It was also verified that the housing program does not follow the normative recommendations and parameters established for the good performance of the buildings, such as the use of linings or slabs. It was noted also that even with the relative amplitude of the comfort zone proposed by Givoni, temperature humidity index of the air, in the studied households, proved unsatisfactory, corroborating the conditions of thermal discomfort of users.